AZAN DAN KAIFIATNYA DI TENGAH WABAH COVID-19 - Muhammad Yusram (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2020)
Azan is an important matter in performing obligatory prayers; it is an announcement of the beginning of five-time daily prayers. However, problems arise when covid-19 pandemic occurs in the midst of society and a particular way (kaifiyat) of azan recommended in the Shari'a is required. The aim of this research was to describe the law and the characteristics of azan during the covid-19 pandemic. Therefore, descriptive qualitative research methods were used in this study so were content analysis techniques and library research approaches in the analysis process. The results of the study show that the law of azan in the midst of the covid-19 pandemic is fardu kifayah (collectively obligatory), while the additional enunciations of azan that was prescribed in the excused condition of the congregational prayer include: Shallu> fi> riha>likum, Shallu> fi> buyu>tikum, Ala> Shallu> fir riha>l, and Ash Shala>h fir Riha>l. The pronouncement of the additional enunciations of azan is after the usual as usual, and this is based on the clearest passage according to the narration of Ibn Umar radhiyallahu anhuma. However, the scholars also allow the muezzin to pronounce those enouncements in place of